Life jimmy carter emagazine (LIFE Jimmy Carter.)
Jimmy Carter, the nation’s longest-lived president, died on December 29, 2024. He leaves a legacy as a peacemaker, reformer, conservationist, and man of faith. During his time in the Oval Office, from 1977 to 1981, the former Georgia farmer was plagued by a bad economy and the seizure of American hostages in Iran. But Carter oversaw the historic Camp David Accords, which led to a peace treaty between Israel and Egypt, helped prevent multiple wars, and set a new standard for how governments should treat their citizens. Carter’s efforts on behalf of peace and human rights continued for decades after his presidency had ended. He established the Carter Center, which helped preserve democracy around the globe, and in 2002, he was awarded the Nobel Peace Prize. The 39th president was also known for his storybook romance with his wife, Rosalynn, whom he met when he was just 3 years old, his close partner until her death in 2023 after 77 years of marriage. This special issue of LIFE celebrates Carter’s journey from the Georgia countryside to White House and beyond, where he set an example of grace, dignity, humility, and service to his country.